New approaches to the archaeology of beekeeping - Wallace-Hare, David (Archaeopress Archaeology, 2022)
Seventeen papers take a holistic view of beekeeping archaeology (including honey, wax, associated products, hive construction, and trade) in one large interconnected geographic region, the Mediterranean, central Europe, and the Atlantic Façade. The book serves as a handbook for current and future researchers considering the archaeology of beekeeping.